Global Understanding of Accretion and Ejection around Black Holes - Mondal, Santanu (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Accretion-ejection around compact objects, mainly around black holes, both in low mass, supermassive, and intermediate-mass, are rich and has been studied exhaustively. However, the subject is expanding and growing rapidly after the launch of different space-based satellites and ground-based telescopes in multiwavelength bands, leaving a range of questions on accretion and ejection mechanisms. The proper understanding of the underlying physical mechanisms responsible for observational evidence is still lacking for several reasons. With the advent of high-resolution satellite observations, it is possible to look at the problems globally as a complete package in a more consistent way. Recently, many new low mass black hole candidates have been discovered; however, very little is known about those systems, e.g., mass, spin parameter, and orbital period. The study in the spectro-temporal domain also needs proper understanding of spectral state change, quasi-periodic oscillation frequency evolution, hardness intensity diagram, and line emissions. The goal and motivation of this book are to focus on top-quality original works in the above-mentioned context, with important research facts that are written in a highly understandable way, from a theoretical, observational, and numerical simulation ground.This book is a collection of high-quality research work, which will give a compact and concise description of the overall view of the subject.